Interlocking liquid containers as makeshift shelter for disaster-affected communities and non-load bearing walls for buildings - Balante, Clarissa M. (Journal in Urban and Regional Planning, 2017)
Access online through this link: https://journals.upd.edu.ph/index.php/SURP/article/view/8931/7868